Tissue-Engineered Small Diameter Arterial Vascular Grafts from Cell-Free Nanofiber PCL/Chitosan Scaffolds in a Sheep Model - Fukunishi, Takuma; Best, Cameron A.; Sugiura, Tadahisa; Shoji, Toshihiro; Yi, Tai; Udelsman, Brooks; Ohst, Devan; Ong, Chin Siang; Zhang, Huaitao; Shinoka, Toshiharu; Breuer, Christopher K.; Johnson, Jed; et al. (PLOS ONE, 2016)
Tissue engineered vascular grafts (TEVGs) have the potential to overcome the issues faced by existing small diameter prosthetic grafts by providing a biodegradable scaffold where the patient’s own cells can engraft and form functional neotissue. However, applying classical approaches to create arterial TEVGs using slow degrading materials with supraphysiological mechanical properties, typically results in limited host cell infiltration, poor remodeling, stenosis, and calcification. The purpose of this study is to evaluate the feasibility of novel small diameter arterial TEVGs created using fast degrading material. A 1.0mm and 5.0mm diameter TEVGs were fabricated with electrospun polycaprolactone (PCL) and chitosan (CS) blend nanofibers. The 1.0mm TEVGs were implanted in mice (n = 3) as an unseeded infrarenal abdominal aorta interposition conduit., The 5.0mm TEVGs were implanted in sheep (n = 6) as an unseeded carotid artery (CA) interposition conduit. Mice were followed with ultrasound and sacrificed at 6 months. All 1.0mm TEVGs remained patent without evidence of thrombosis or aneurysm formation. Based on small animal outcomes, sheep were followed with ultrasound and sacrificed at 6 months for histological and mechanical analysis. There was no aneurysm formation or calcification in the TEVGs. 4 out of 6 grafts (67%) were patent. After 6 months in vivo, 9.1 ± 5.4% remained of the original scaffold. Histological analysis of patent grafts demonstrated deposition of extracellular matrix constituents including elastin and collagen production, as well as endothelialization and organized contractile smooth muscle cells, similar to that of native CA. The mechanical properties of TEVGs were comparable to native CA. There was a significant positive correlation between TEVG wall thickness and CD68+ macrophage infiltration into the scaffold (R2 = 0.95, p = 0.001). The fast degradation of CS in our novel TEVG promoted excellent cellular infiltration and neotissue formation without calcification or aneurysm. Modulating host macrophage infiltration into the scaffold is a key to reducing excessive neotissue formation and stenosis.